Kompleksitas Obyek dan Running-Wheel Mempengaruhi Novel Object Recognition Test pada Mencit (Mus musculus) - HANIM, NISFA; WIDYASTUTI, SALMAH; ALFIYAN, ACHMAD; AKBAR, MUHAMMAD AZHARI; JULIANDI, BERRY (Jurnal Sumberdaya Hayati, 2018)
This research aimed to confirm the tendency of mice to novel object, effect of exercise (in running-wheel) toward memory of mice and to test tendency of mice in avoiding predator signal in novel object. Novel object recognition test (NORT) used to test the memory the day after acquisition phase (NORT I) and memory one week after exercise was given (running-wheel) (NORT II). The result showed that there was no tendency of mice in exploring toward novel object in both NORT I and NORT II. This might happen because the complexity of familiar object higher than novel object, so the familiar object could accommodate more activities. Exercise using running-wheel in mice had an effect on memory, it could be seen in decreasing duration of object exploration time from NORT I to NORT II. There was no tendency in avoiding predator’s signal on novel object which was attached by urine addition (odor signal).